Cervical Cancer Awareness: An Information Dissemination Campaign In Indonesia - Dedeh Sri Rahayu; Marcos Ochoa (Jurnal Keperawatan Padjadjaran, 2015)
This  descriptive-correlational study  was  conducted  to  determine  the level  of  cervical cancer  awareness of 196 participants who were conveniently recruited from selected regions in South Cimahi, Melong, West Java,Indonesia. The survey was conducted on February 2014 for fifteen (15) days using a survey questionnaire for  data  collection.  Descriptive  statistics  such  as  frequency  and  percentage  distribution  were  used  for demographic profile and weighted mean for the assessment of the level of awareness on cervical cancer, and inferential statistics such as Pearson r and chi square for   hypothesis testing. They have moderate awareness on basic information on cervical cancer, foremost are the areas on prevention, anatomy, treatment and common diagnostic examination, but with very little knowledge or partial awareness on the items pertaining to signs and symptoms, etiology and mode of transmission of cervical cancer. The results of chi square and pearson r tests found that the participants’ gender and educational attainment were not significantly correlated with their level of awareness on cervical cancer while, family monthly income was significantly correlated to their level of awareness.  Hence, this study concluded that gender and educational attainment do not necessarily determine a person’s level of awareness or knowledge but family income could contribute to their level of awareness. The study findings formed the basis of designing an information dissemination campaign material on cervical cancer among the residents of South Cimahi, Indonesia. In this regard, an intensive information dissemination campaign  program  on  cervical  cancer  is  recommended  using  the  proposed  campaign  material  designed.Key words: Campaign, cervical cancer, detection, dissemination. Kampanye di Indonesia: Deteksi Dini Kanker Serviks AbstrakPenelitian deskriptif-korelasional ini dilakukan untuk mengetahui tingkat kesadaran 196 peserta yang nyaman direkrut dari daerah tertentu di Cimahi Selatan, Melong, Jawa Barat, Indonesia. Pengumpulan data menggunakan kuesioner. Statistik deskriptif digunakan untuk profil demografis dan rata-rata untuk penilaian tingkat kesadaran mengenai kanker serviks, dan statistik inferensi seperti Pearson r dan Chi square untuk pengujian hipotesis. Hasil  penelitian menunjukkan bahwa  responden  memiliki kesadaran  moderat  pada  informasi  dasar  tentang kanker serviks, terutama adalah daerah tentang pencegahan, anatomi, pengobatan dan pemeriksaan diagnostik umum,  tetapi  dengan  sedikit  pengetahuan  atau  kesadaran  parsial  pada  item  yang  berkaitan  dengan  tanda- tanda dan gejala, etiologi dan cara penularan kanker serviks. Kemudian ditunjukkan bahwa gender dan pendidikan  pencapaian  peserta  tidak  signifikan  berkorelasi  dengan  tingkat  kesadaran  pada  saat  kanker serviks,  pendapatan  bulanan  keluarga  secara  signifikan berhubungan  dengan  tingkat  kesadaran.  Penelitian ini  menyimpulkan  bahwa  gender  dan  pencapaian  pendidikan  tidak  selalu  menentukan  tingkat  kesadaran seseorang atau pengetahuan tetapi pendapatan keluarga dapat memberikan kontribusi untuk tingkat kesadaran.Kata kunci: Deteksi, disseminasi, kampanye, kanker serviks.